1997
DOI: 10.1523/jneurosci.17-19-07385.1997
|View full text |Cite
|
Sign up to set email alerts
|

Purkinje Cell Expression of a Mutant Allele ofSCA1in Transgenic Mice Leads to Disparate Effects on Motor Behaviors, Followed by a Progressive Cerebellar Dysfunction and Histological Alterations

Abstract: Spinocerebellar ataxia type 1 (SCA1) is an autosomal dominant neurological disorder caused by the expansion of a CAG repeat encoding a polyglutamine tract. Work presented here describes the behavioral and neuropathological course seen in mutant SCA1 transgenic mice. Behavioral tests indicate that at 5 weeks of age mutant mice have an impaired performance on the rotating rod in the absence of deficits in balance and coordination. In contrast, these mutant SCA1 mice have an increased initial exploratory behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
262
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 266 publications
(282 citation statements)
references
References 26 publications
19
262
1
Order By: Relevance
“…This study was performed on naïve animals only. Mice were placed on the rotarod apparatus (Ugo Basile) for four trials per day for 4 consecutive days (Clark et al, 1997). Each trial lasted a maximum of 10 min, divided into an initial part in which the rotarod underwent a linear acceleration from 4-40 rpm over the first 5 min of the trial and then remained at maximum speed for the remaining 5 min.…”
Section: Accelerating Rotarod Testmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was performed on naïve animals only. Mice were placed on the rotarod apparatus (Ugo Basile) for four trials per day for 4 consecutive days (Clark et al, 1997). Each trial lasted a maximum of 10 min, divided into an initial part in which the rotarod underwent a linear acceleration from 4-40 rpm over the first 5 min of the trial and then remained at maximum speed for the remaining 5 min.…”
Section: Accelerating Rotarod Testmentioning
confidence: 99%
“…After coating the hind feet of the mice with a non-toxic paint, animals were allowed to walk through a dark, 40-cm long, 9-cm wide, 6-cm high tunnel, and the footprint patterns made on the paper lining the floor of the tunnel were scored for four step parameters (Clark et al, 1997).…”
Section: Footprint Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 This mouse, known as the B05 model, develops progressive disease, with many features similar to SCA1 including measurable gait deficits by 7 weeks of age. Additionally, there are transcriptional changes by postnatal day 25 and PC loss by 24 weeks of age.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there are transcriptional changes by postnatal day 25 and PC loss by 24 weeks of age. 3 Earlier, a doxycycline-inducible form of the B05 model revealed that pre-existing phenotypes were reversible after many weeks of mutant ATXN1 expression. 4 This suggests that a window of opportunity exists not only for halting the disease, but perhaps also to reverse the presence or severity of symptoms once present.…”
Section: Introductionmentioning
confidence: 99%